2018
DOI: 10.1002/pro.3487
|View full text |Cite
|
Sign up to set email alerts
|

Flavin oxidation in flavin‐dependent N‐monooxygenases

Abstract: Siderophore A (SidA) from Aspergillus fumigatus is a flavin-containing monooxygenase that hydroxylates ornithine (Orn) at the amino group of the side chain. Lysine (Lys) also binds to the active site of SidA; however, hydroxylation is not efficient and H O is the main product. The effect of pH on steady-state kinetic parameters was measured and the results were consistent with Orn binding with the side chain amino group in the neutral form. From the pH dependence on flavin oxidation in the absence of Orn, a pK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
(74 reference statements)
2
13
0
Order By: Relevance
“…It has been previously shown that the pK a of the flavin N5 atom in SidA is modulated to stabilize the C4a-hydroperoxyflavin or to facilitate flavin oxidation. 24 We determined the pK a values for M101A in the absence of L-Orn, This interpretation is in agreement with the proposal of Setser et al that the purpose of the FAD conformational change from in to out is to eject NADP + in the last step of catalysis. 8 The M101A−NADP + complex perhaps represents a deadend state that is avoided by the wild-type enzyme but is made…”
supporting
confidence: 90%
“…It has been previously shown that the pK a of the flavin N5 atom in SidA is modulated to stabilize the C4a-hydroperoxyflavin or to facilitate flavin oxidation. 24 We determined the pK a values for M101A in the absence of L-Orn, This interpretation is in agreement with the proposal of Setser et al that the purpose of the FAD conformational change from in to out is to eject NADP + in the last step of catalysis. 8 The M101A−NADP + complex perhaps represents a deadend state that is avoided by the wild-type enzyme but is made…”
supporting
confidence: 90%
“…DFT studies with SidA in complex with ornithine or lysine were consistent with homolytic cleavage of the Fl 4a -OOH and hydroxylation by hydroxyl radical transfer. The studies also suggested that ornithine binds with the N5-atom in the deprotonated form, which was later supported by pH studies [60]. The hydroxyl radical mechanism provides a logical explanation for the substrate selectivity of SidA.…”
Section: Hydroxylation Mechanismmentioning
confidence: 76%
“…NMOs have been under investigation for many years with the best characterized examples being the l -ornithine monooxygenases SidA from Aspergillus fumigatus and PvdA from Pseudomonas aeruginosa. , , These enzymes perform a single hydroxylation of the N-atom on the side chain of l -ornithine forming hydroxylamine, which is part of the hydroxamate moiety of siderophores. Despite their prevalence in natural product pathways, little is known about NMOs outside of siderophore biosynthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the amino acid sequences of FzmM, CreE (51% identity), SidA (15% identity), PvdA (14% identity), and KtzI (14% identity), a structural-characterized ornithine hydroxylase, were aligned to determine amino acid conservation (Figure ). Residues R121, Q80, and S610 of FzmM were aligned to R144, Q102, and S469 of SidA, which have been shown to be associated with FAD binding or C­(4a)-hydroperoxyflavin stabilization. , The FAD-binding motif GXGXXG and some residues that are structurally associated with FAD binding such as P26 and W64 (P49 and W90 in SidA) are also present. , Key residues involved in NADPH binding in NMOs were absent in the FzmM amino acid sequence. This includes the SidA residues: R279 which is involved in NADPH selectivity, S257 essential for NADP + orientation, the Tyr-loop which undergoes major conformational changes as a part of NADPH binding, and the signature NMO “(F/V)­ATGY” motif. ,,, The absence of these is significant as it suggests that dinucleotide substrate binding utilizes different structural features than that described in other NMOs.…”
Section: Discussionmentioning
confidence: 99%